Wear and its effects on dental topography measures in howling monkeys (Alouatta palliata). Issue 4 (16th September 2016) - Pampush, James D.; Spradley, Jackson P.; Morse, Paul E.; Harrington, Arianna R.; Allen, Kari L.; Boyer, Doug M.; Kay, Richard F.
Abstract: Objectives: Three dental topography measurements: Dirichlet Normal Energy (DNE), Relief Index (RFI), and Orientation Patch Count Rotated (OPCR) are examined for their interaction with measures of wear, within and between upper and lower molars in Alouatta palliata . Potential inferences of the "dental sculpting" phenomenon are explored. Materials and methods: Fifteen occluding pairs of howling monkey first molars (15 upper, 15 lower) opportunistically collected from La Pacifica, Costa Rica, were selected to sample wear stages ranging from unworn to heavily worn as measured by the Dentine Exposure Ratio (DER). DNE, RFI, and OPCR were measured from three‐dimensional surface reconstructions (PLY files) derived from high‐resolution CT scans. Relationships among the variables were tested with regression analyses. Results: Upper molars have more cutting edges, exhibiting significantly higher DNE, but have significantly lower RFI values. However, the relationships among the measures are concordant across both sets of molars. DER and EDJL are curvilinearly related. DER is positively correlated with DNE, negatively correlated with RFI, and uncorrelated with OPCR. EDJL is not correlated with DNE, or RFI, but is positively correlated with OPCR among lower molars only. Discussion: The relationships among these metrics suggest that howling monkey teeth adaptively engage macrowear. DNE increases with wear in this sample presumably improving food breakdown. RFI is initially high but declines with wear, suggesting that the initially high RFI safeguards against dental senescence. OPCR values in howling monkey teeth do not show a clear relationship with wear changes.